Inter-social-networking: accounting for multiple identities - Price, Dominic; McAuley, Derek; Mortier, Richard; Greenhalgh, Chris; Brown, Michael; Angelopoulos, Spyros (Springer International Publishing, 2015)
We argue that the current approaches to online social networking give rise to numerous challenges regarding the management of the multiple facets of people’s digital identities within and around social networking sites (SNS). We propose an architecture for enabling people to better manage their SNS identities that is informed by the way the core Internet protocols developed to support interoperation of proprietary network protocols, and based on the idea of Separation of Concerns [1]. This does not require modification of existing services but is predicated on providing a connecting layer over them, both as a mechanism to address problems of privacy and identity, and to create opportunities to open up online social networking to a much richer set of possible interactions and applications.